2010
DOI: 10.1051/0004-6361/200913949
|View full text |Cite
|
Sign up to set email alerts
|

1318 new variable stars in a 0.25 square degree region of the Galactic plane

Abstract: analysis method as implemented in the pysis3 code and resulted in more than 500 000 lightcurves of stars down to a magnitude limit of R ∼ 24.5. A search for variable stars resulted in the detection of 1318 variables of different types. 1011 of these are eclipsing or contact binary stars. A number of the contact binaries have low mass-ratios and several of the detached binaries appear to have low-mass components. Three candidate contact binaries have periods at the known cut off including two with periods lower… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Maceroni & Montalbán () found an almost twin M3 system (OGLE BW3 V38; semi‐detached, P = 0.1984 d) with strong chromospheric emission and masses of 0.44 and 0.41 M ⊙ . Other surveys found only binaries with P > 0.21 d. Miller et al () found seven candidate contact binaries with periods between 0.2109 and 0.23 d in a 0.25 deg 2 Galactic plane survey with the European Southern Observatory 2.2‐m telescope, and Weldrake et al () found a P = 0.2155 d system in the globular cluster 47 Tuc, whereas Pribulla, Vanko & Hambalek () report a P = 0.211249 d system. The left‐hand panel of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Maceroni & Montalbán () found an almost twin M3 system (OGLE BW3 V38; semi‐detached, P = 0.1984 d) with strong chromospheric emission and masses of 0.44 and 0.41 M ⊙ . Other surveys found only binaries with P > 0.21 d. Miller et al () found seven candidate contact binaries with periods between 0.2109 and 0.23 d in a 0.25 deg 2 Galactic plane survey with the European Southern Observatory 2.2‐m telescope, and Weldrake et al () found a P = 0.2155 d system in the globular cluster 47 Tuc, whereas Pribulla, Vanko & Hambalek () report a P = 0.211249 d system. The left‐hand panel of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have classified 1318 LCs of eclipsing binaries along with some possible pulsating stars in the Galaxy which lie primarily along the spiral arms. k-medoids method in combination with CID has been employed for crossverification of the subjectively classified variable stars (Miller et al 2010), gives rise to two clusters k1 and k2, where the resulting clustering has been assessed as quite good in terms of ASW. We observe that k1 consists of all three categories EB, EW and PUL in very close number, whereas the number of EA is comparatively small.…”
Section: Resultsmentioning
confidence: 99%
“…During the past decades many photometric surveys ( The above observations are generally related to Galactic Bulge, Magellanic clouds or globular cluster surveys. Miller et al (2010) have carried out observations of Es (along with some possible pulsating stars) covering 0.25 square degree region of the Galactic plane centered on Galactic coordinates (l, b) of (330.94, −2.28) deg. The majority of stars in the above region are thought to be associated with the Normal Spiral Arm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations